LOSING LATIN AMERICA - Ellner, By Steve (La Sociología en sus Escenarios, 2012)
Resumen. El abandono por parte del Presidente Obama, de la tradición liberal en su postura en América latina ha sido consecuencia de la necesidad de aplacar a sus críticos derechistas. Por ejemplo: el cambio sobre el acuerdo de libre comercio con Colombia por encima de las posiciones internas en contra. La capitulación a las exigencias de la derecha en Honduras. Otro incidente que demostró la capacidad de republicanos de establecer la agenda en Washington, así como las vacilaciones de la administración de Obama, era el nombramiento de Larry Palmer como embajador a Venezuela. A pesar de convergencias, el estilo y las políticas de Obama en América latina son apenas indistinguibles a ls viejas políticas de los republicanos en América Latina.a la su derecha. Obama todo-sonríe encuentro con Chávez en 2009 y Clinton en enero de este año reforzó la noción del presidente del contrato con los enemigos, absolutamente diferente usted de George W. Bush de "está conmigo o contra mí" el acercamiento. Finalmente, esta línea de pensamiento privilegia naciones como Colombia, Chile y México como aliados especiales simplemente porque aceptan fórmulas financieras aprobadas por políticas monetarias internacionales y de libre cambio con los Estados Unidos. Tales preferencias dividen el continente en la mitad y la distancia América de países como la Argentina y el Brasil, cuyo nacionalismo no están siempre a gusto de Washington. Abstract. President Obama's abandonment of the liberal tradition in his stance on Latin America has been driven by the perceived need to placate rightist critics. For example: pressed for quick passage of a free trade agreement with Colombia, and since then has followed up on the proposal. Obama's change-from opposition to the free trade agreement with Colombia, to lukewarm endorsement of it, to vigorous support-is just one example of his turnabout on Latin American policy. Capitulation to the right on Honduras. Another incident that demonstrated the ability of Republicans to set the agenda in Washington, as well as the vacillations of the Obama administration, was the appointment of Larry Palmer as ambassador to Venezuela.In spite of convergences, Obama's style and policies on Latin America are hardly indistinguishable from Republicans to his right. Obama's all-smile encounter with Chávez in 2009 and Clinton's in January of this year reinforced the president's notion of engagement with enemies, quite different from George W. Bush's "you're with me or against me" approach.Finally, Washington needs to cease equating the open-market economic policies it advocates with democracy. This line of thinking privileges nations like Colombia, Chile and Mexico as special allies simply because they accept International Monetary Fund-approved formulas and free trade with the United States. Such preferences divide the continent in half and distance America from countries like Argentina and Brazil, whose assertions of nationalism are not always to Washington's liking. The hardliners will rant and rave about any type of renovation of U.S. foreign policy along these lines, but it may represent an important first step in regaining the respect and good will of what used to be called our backyard.